2007
DOI: 10.1111/j.1467-8624.2007.01042.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences and the Development of Joint Attention in Infancy

Abstract: This study examined the development of joint attention in 95 infants assessed between 9 and 18 months of age. Infants displayed significant test -retest reliability on measures of following gaze and gestures (responding to joint attention, RJA) and in their use of eye contact to establish social attention coordination (initiating joint attention, IJA). Infants displayed a linear, increasing pattern of age-related growth on most joint attention measures. However, IJA was characterized by a significant cubic dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

33
405
8
14

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 515 publications
(460 citation statements)
references
References 77 publications
33
405
8
14
Order By: Relevance
“…This conclusion is in line with the developmental data from Reboul (2003) and other data suggesting a clear link between joint attention and language development (e.g., Mundy et al, 2007). Whereas infants knew only a few to a couple of dozen words at the moment they were developing their joint attentional skills (from 9 to 18 months of age), this number rapidly increased to over 300 in the following half year, when they were able to use these skills.…”
Section: Discussionsupporting
confidence: 79%
See 3 more Smart Citations
“…This conclusion is in line with the developmental data from Reboul (2003) and other data suggesting a clear link between joint attention and language development (e.g., Mundy et al, 2007). Whereas infants knew only a few to a couple of dozen words at the moment they were developing their joint attentional skills (from 9 to 18 months of age), this number rapidly increased to over 300 in the following half year, when they were able to use these skills.…”
Section: Discussionsupporting
confidence: 79%
“…Carpenter et al (1998) found that the order in which the three stages arise is: checking attention (month 9-10), followed by following attention (month 10.5) and only then directing attention (month 12.6). This ordering that has been confirmed in other studies for autistic children (Carpenter, Pennington & Rogers, 2002) and healthy children (Mundy et al, 2007). Moreover, the frequency with which children use these three attentional mechanisms between 9 and 18 months of age predicts how well these children perform at language development tests at 24 months (Mundy et al, 2007).…”
Section: Introductionsupporting
confidence: 71%
See 2 more Smart Citations
“…Joint attention is said to be important in language learning, because children need social cues like the eye gaze of a social partner to map new words to objects (Baldwin, 2000). Research has found concurrent and longitudinal associations between joint attention and language in typical children (Mundy et al, 2007) and children with ASD (Charman, 2003;Schietecatte, Roeyers, & Warreyn, 2012). Pretend play and language are theoretically associated because they both rely on a symbolic representation ability (Lewis, 2003).…”
mentioning
confidence: 99%